Public advocates, private advisors: the autonomy, function, and influence of the President's Council of Advisors on Science and Technology - Kenneth M. Evans; Kenneth M. Evans; Kirstin R. W. Matthews (Frontiers in Research Metrics and Analytics)
US national expert advisory bodies related to science, technology, and innovation (STI) policy have a wide range of missions, governing structures, operational practices, cultures, and impact on federal policymaking. This paper offers an analytical framework for assessing the autonomy, function, and influence of the President's Council of Advisors on Science and Technology (PCAST), a federal advisory committee consisting of 30 elite scientists, engineers, and industry leaders appointed by and advising the president. We demonstrate that PCAST carries both a strong instrumental advisory role, providing substantive advice to White House STI policy development, and a significant symbolic advisory role, offering visible public support to presidential decisions and initiatives related to STI. However, we find that the council's engagement with either or both roles has shifted depending on its available resources, the policy agenda of the administration it serves, the level of presidential attention, and the priorities of council leadership. The paper concludes with recommendations to guide future PCASTs in fulfilling their mission and appropriately influencing US national STI policy.